CAPACITY PLANNING AS A RESPONSIVE STRATEGY TO PRODUCTION DEMAND IN SMEs - Haryadi Sarjono; Bella Vannesa; Chelsea Gianina (Jurnal Manajemen dan Bisnis Performa, 2026)
This study aims to analyze capacity planning at Dolces Bites, a small and medium-sized enterprise (SME) in the culinary sector, in order to improve operational performance and anticipate fluctuations in consumer demand. The main challenge faced by the company is demand variability and limited production resources, which may create bottlenecks in specific processes. The research employs a quantitative approach by calculating design capacity, effective capacity, utilization, efficiency, and bottleneck identification based on production data from December 2024 to May 2025. The findings reveal that Dolces Bites experienced relatively low utilization rates at the beginning of the observed period, ranging from 29% to 50%, but showed a significant increase in April and May 2025, reaching 83.33%. Production efficiency remained relatively stable between 70% and 91%, indicating the company’s ability to achieve operational targets despite underutilized capacity. Bottleneck analysis shows that the packaging process carries the highest workload (60%), making it the primary constraint within the production chain. Based on these results, the recommended capacity planning strategy is the match strategy, which adjusts capacity gradually in line with demand trends. This approach is considered the most suitable for SMEs, as it ensures flexibility, minimizes the risk of overcapacity, and supports sustainable business growth.